Food-Grade Polar Extracts from Sea Fennel (Crithmum maritimum L.) By-Products: Unlocking Potential for the Food Industry - Aizhan Ashim; Lama Ismaiel; Benedetta Fanesi; Ancuta Nartea; Antonietta Maoloni; Oghenetega Lois Orhotohwo; Helen Stephanie Ofei Darko; Paolo Lucci; Lucia Aquilanti; Deborah Pacetti; Roberta Pino; Rosa Tundis; et al. (Foods)
Crithmum maritimum L. is a halophyte with antioxidant and antimicrobial potential for the food industry. Pruning generates a by-product composed of woody stems, old leaves, and flowers. To valorize this underutilized and largely unexplored biomass, food-grade polar extraction (hydroethanolic vs. aqueous) was applied. The extracts were characterized for their bioactive compounds (polyphenols, tocopherols, carotenoids, total phenols (TPC) and total flavonoids (TFC)). Further, the extracts were assessed for their in vitro antioxidant activity (ABTS, DPPH, FRAP, and β-carotene bleaching) and antimicrobial activity against eight target strains ascribed to Escherichia coli, Staphylococcus aureus, and Listeria innocua. The hydroethanolic extract exhibited higher concentration of bioactives compared to the water extract and raw by-product. The β-carotene bleaching test revealed that both extracts are potent inhibitors of lipid peroxidation. The aqueous extract showed no antimicrobial activity, while the ethanolic extract exhibited strain-dependent behavior against S. aureus and L. innocua but not E. coli. The minimum inhibitory concentration and the minimum bactericidal concentration of the ethanolic extract against S. aureus were 2.5 MIC and 10.0 MBC mg/mL, respectively. Ethanolic extracts could potentially be used in food formulations to enhance lipid peroxidation resistance and antimicrobial capacity as food-grade natural preservatives.